Kajian Filantropi di Indonesia: Studi Undang-Undang Pengumpulan Uang Atau Barang dan Undang-Undang Zakat - Prassetyo, Erik Dwi; Aulia, Layla (UIN Sunan Kalijaga Yogyakarta, 2022)
Philanthropy is an important aspect that can improve people's welfare, therefore the government must make regulations regarding good philanthropy by existing legal requirements. However, the current regulations, namely the regulations CMG and the Zakat regulations, are considered to still have weaknesses, as well as the large philanthropic benefits that exist will be difficult to achieve. This research focuses on a comparative study between the rules CMG and the Zakat regulations with the main issues being the first, how philanthropy is regulated in the two regulations, and second, how the comparison is between the two. This research is a type of normative legal research (library) with a comparative method and statutory approach. The source of this research data is from laws, books, or journals that are relevant to the discussion. The results of this study indicate that philanthropic arrangements in Zakat regulations are more ideal and effective when compared to regulations CMG which still have many weaknesses. These weaknesses can be seen from aspects of technology utilization, requirements, reporting, financing of organizational activities, guidance and supervision, and finally related to sanctions. It seems that it can be seen that both laws regulate provisions regarding licensing, accountability, and law enforcement. Meanwhile, the difference is that there are no regulations regarding the CMG, provisions regarding licensing requirements, community participation, special management, guidance and supervision agencies, administrative sanctions, as well as provisions on the number of criminal sanctions and fines.